Continual measurement of arterial dP/dt(max) enables minimally invasive monitoring of left ventricular contractility in patients with acute heart failure - Ostadal, Petr (Crit Care, 2019)
BACKGROUND: Continuous, reliable evaluation of left ventricular (LV) contractile function in patients with advanced heart failure requiring intensive care remains challenging. Continual monitoring of dP/dt(max) from the arterial line has recently become available in hemodynamic monitoring. However, the relationship between arterial dP/dt(max) and LV dP/dt(max) remains unclear. This study aimed to determine the relationship between arterial dP/dt(max) and LV dP/dt(max) assessed using echocardiography in patients with acute heart failure. METHODS: Forty-eight patients (mean age 70.4 years [65% male]) with acute heart failure requiring intensive care and hemodynamic monitoring were recruited. Hemodynamic variables, including arterial dP/dt(max), were continually monitored using arterial line pressure waveform analysis. LV dP/dt(max) was assessed using continuous-wave Doppler analysis of mitral regurgitation flow. RESULTS: Values from continual arterial dP/dt(max) monitoring were significantly correlated with LV dP/dt(max) assessed using echocardiography (r = 0.70 [95% confidence interval (CI) 0.51–0.82]; P < 0.0001). Linear regression analysis revealed that LV dP/dt(max) = 1.25 × (arterial dP/dt(max)) (P < 0.0001). Arterial dP/dt(max) was also significantly correlated with stroke volume (SV) (r = 0.63; P < 0.0001) and cardiac output (CO) (r = 0.42; P = 0.0289). In contrast, arterial dP/dt(max) was not correlated with SV variation, dynamic arterial elastance, heart rate, systemic vascular resistance (SVR), or mean arterial pressure. Markedly stronger agreement between arterial and LV dP/dt(max) was observed in subgroups with higher SVR (N = 28; r = 0.91; P <  0.0001), lower CO (N = 26; r = 0.81; P <  0.0001), and lower SV (N = 25; r = 0.60; P = 0.0014). A weak correlation was observed in the subjects with lower SVR (N = 20; r = 0.61; P = 0.0004); in the subgroups with higher CO (N = 22) and higher SV (N = 23), no significant correlation was found. CONCLUSION: Our results suggest that in patients with acute heart failure requiring intensive care with an arterial line, continuous calculation of arterial dP/dt(max) may be used for monitoring LV contractility, especially in those with higher SVR, lower CO, and lower SV, such as in patients experiencing cardiogenic shock. On the other hand, there was only a weak or no significant correlation in the subgroups with higher CO, higher SV, and lower SVR.